2005
DOI: 10.1074/mcp.m400087-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteome Analysis of Saccharomyces cerevisiae Grown in Chemostat Cultures Limited for Glucose or Ethanol

Abstract: The use of chemostat culturing enables investigation of steady-state physiological characteristics and adaptations to nutrient-limited growth, while all other relevant growth conditions are kept constant. We examined and compared the proteomic response of wild-type Saccharomyces cerevisiae CEN.PK113-7D to growth in aerobic chemostat cultures limited for carbon sources being either glucose or ethanol. To obtain a global overview of changes in the proteome, we performed triplicate analyses using two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 40 publications
(41 reference statements)
8
55
1
Order By: Relevance
“…Since it has been reported that the central carbon metabolism of S. cerevisiae is controlled to a large extent via posttranscriptional mechanisms in chemostat studies (11,32,33), quantitative RT-PCR was not carried out to substantiate our findings concerning the involvement of the central carbon metabolism in cellular response to the presence of furfural. Instead, the levels of intracellular NADH, NAD Ï© , NADH/ NAD Ï© , and ATP/ADP were measured by LC/MS (Fig.…”
Section: Glycolysis Pathwaymentioning
confidence: 77%
“…Since it has been reported that the central carbon metabolism of S. cerevisiae is controlled to a large extent via posttranscriptional mechanisms in chemostat studies (11,32,33), quantitative RT-PCR was not carried out to substantiate our findings concerning the involvement of the central carbon metabolism in cellular response to the presence of furfural. Instead, the levels of intracellular NADH, NAD Ï© , NADH/ NAD Ï© , and ATP/ADP were measured by LC/MS (Fig.…”
Section: Glycolysis Pathwaymentioning
confidence: 77%
“…This study revealed that metabolic fluxes in the acetate and glycerol pathway were significantly different in cells growing on xylose compared with those growing on glucose. Kolkman et al studied yeast grown in chemostat cultures limited for glucose and ethanol [44], which enabled the differential analysis of protein expression levels under glycolytic and gluconeogenic conditions. By using multiple 2D gels (Figure 1c,d) it was possible to perform a decent statistical analysis to determine significant changes in protein expression levels.…”
Section: Quantification Strategies 2d-gel-based Quantificationmentioning
confidence: 99%
“…Data obtained in a microarray analysis of organisms grown in a chemostat have been shown to be more reproducible and accurate than batch culture DNA array data (6,12,13,17). A combination of a chemostat culture and DNA microarrays was used previously to study the effects of oxygen limitation on the gene expression profile of M. tuberculosis (2).…”
mentioning
confidence: 99%